2014
DOI: 10.2119/molmed.2014.00136
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Migration Inhibitory Factor (MIF) Enzymatic Activity and Lung Cancer

Abstract: The cytokine macrophage migration inhibitory factor (MIF) possesses unique tautomerase enzymatic activity, which contributes to the biological functional activity of MIF. In this study, we investigated the effects of blocking the hydrophobic active site of the tautomerase activity of MIF in the pathogenesis of lung cancer. To address this, we initially established a Lewis lung carcinoma (LLC) murine model in Mif-KO and wild-type (WT) mice and compared tumor growth in a knock-in mouse model expressing a mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 36 publications
1
47
0
Order By: Relevance
“…For our in vitro assays, we used recombinant human MIF (rMIF), a kind donation from R. Bucala (Yale School of Medicine, Yale University, New Haven, CT, USA). We have previously published our work on the development of an in-house novel small-molecular-weight inhibitor for MIF's enzymatic activity: SCD-19 [3-(29-methylphenyl)-isocoumarin] (12). ISO-1 [(S,R)-3-(4-hydroxyphenyl)4.5-dihydro-5-isoxazole acetic acid methyl ester] is a commercially available inhibitor (VWR, Dublin, Ireland).…”
Section: Recombinant Proteins and Inhibitorsmentioning
confidence: 99%
“…For our in vitro assays, we used recombinant human MIF (rMIF), a kind donation from R. Bucala (Yale School of Medicine, Yale University, New Haven, CT, USA). We have previously published our work on the development of an in-house novel small-molecular-weight inhibitor for MIF's enzymatic activity: SCD-19 [3-(29-methylphenyl)-isocoumarin] (12). ISO-1 [(S,R)-3-(4-hydroxyphenyl)4.5-dihydro-5-isoxazole acetic acid methyl ester] is a commercially available inhibitor (VWR, Dublin, Ireland).…”
Section: Recombinant Proteins and Inhibitorsmentioning
confidence: 99%
“…Blocking of MIF activity either by antibodies or stable RNA interference reduced tumor growth in animal models of colorectal cancer [29], prostate cancer [30], ovarian cancer [20], neuroblastoma [31], pancreatic cancer [10], breast cancer [9], melanoma [22, 32] and lung cancer [28]. The involvement of MIF in human tumor development has been substantiated by reports that describe higher MIF levels in the circulation of cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study also implicated MIF as being involved in electrical remodeling that accompanies AF, probably by decreasing I Ca,L amplitudes through impairment of channel function, down-regulation of LCC α 1C subunit levels, and activation of cSrc kinases in atrial myocytes [121]. Several reports also identified that blocking the function of MIF significantly attenuated cancer growth in vitro or in vivo systems, such as with lung cancer, thyroid cancer, bladder cancer, squamous carcinoma, melanoma, and colon cancer [171][172][173][174][175]. MIF inhibition is deleterious for high-fat diet-induced cardiac dysfunction and antagonizes pressure overload-induced cardiac hypertrophy [176,177].…”
Section: Macrophage Migration Inhibitory Factor (Mif)mentioning
confidence: 99%